Impact of CEO's characteristics on investment decisions of Indian listed firms: Does crisis make any difference? - Gaurav Gupta; Jitendra Mahakud; Byomakesh Debata (Cogent Economics & Finance, 2018)
Using a sample of listed Indian manufacturing companies, this study examines the role of chief executive officer's (CEO's) personal characteristics like age, tenure, education, and career experience in the determination of investment decisions of the firm. The dynamic panel data model estimation, more specifically the system generalized method of moments estimation results reveal a negative relation between CEO's age and corporate investment. CEO's financial education is positively associated with investment decisions. The investment cash flow sensitiv- ity analysis posits that CEO's age and financial education reduce the sensitivity of investment with respect to cash flow. The results are robust across different periods, defined on the basis of crises. In times of financial crisis, we document that firm's liquidity and age, CEO's career experience and tenure turn out to be significant de- terminants of corporate investment. This paper provides an out-of-sample evidence of the role of CEO's personal characteristics on the determination of corporate investment, which is an unexplored issue from an emerging market perspective.
Keywords: 330; CEO age; cash flow; career experience; chief executive officer; corporate investment; financial education; generalized method of moments